USE OF CREATIVE AND PRODUCTIVE LEARNING MODELS TO INCREASE MOTIVATION AND INDONESIAN LEARNING RESULTS AT SD NEGERI 200201 PADANGSIDIMPUAN - Annahari (PANTAK: Jurnal Penelitian Tindakan Kelas, 2024)
Based on research findings, there are consequences that can be produced, namely (a) Creative and productive learning models have been proven to increase student motivation and learning outcomes in Indonesian, therefore this model continues to be used in learning activities in schools to improve the quality of learning this language . (b) For teachers, creative and productive learning models in Indonesian language subjects can be used as alternative learning methods in an effort to improve student learning outcomes. Therefore, it is hoped that schools will be proactive in helping teachers and students meet their needs in an effort to improve the quality of educational services. Apart from that, it is hoped by researchers that this research will provide additional knowledge and at the same time provide new ideas about the process of learning development and innovation at the basic education level. The results of the observation sheet show that student motivation and learning outcomes in Indonesian at the end of Cycle II have reached the very good category, namely the results of observing motivation and student learning outcomes are 100%. Student learning outcomes can be improved with creative and productive learning models. This is proven by the student learning results in Cycle I, where 27 students, or 87.09%, met the KKM, and 4 students, or 12.91%, did not meet the KKM. In Cycle II, student learning outcomes were better, with 31 students, or 100%, meeting the KKM.